Tumour budding in rectal cancer. A comprehensive review - Lino-Silva, Leonardo S. (Contemp Oncol (Pozn), 2018)
A unique and fundamental characteristic of malignant neoplastic cells is their ability to invade other tissues and metastasise. The first step in this process is the dissociation of some of these cells from the tumour invasion front, named tumour budding (TB). This phenomenon has become increasingly relevant in recent years due to its association with adverse clinicopathological characteristics and with the epithelial-mesenchymal transition. TB has been studied by mixing colon with rectal tumours, but it is clinically important to differentiate these types of tumours. A review in two databases without language restriction was performed from 1950 to 2017 about TB with an emphasis on rectal cancer. We present various aspects of TB, from its terminology and evaluation to its molecular aspects, through its clinical associations. TB is associated with adverse clinicopathological features, like lymphovascular invasion, lymph node metastasis, and decreased survival. More studies of the clinicopathological, molecular, and epidemiological characteristics of TB in rectal cancer are needed.